2005
DOI: 10.1097/01.brs.0000174279.44855.02
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome in Neck and Shoulder Symptoms

Abstract: The results found in this study indicate that besides clinical characteristics, psychological factors also predict the outcome of neck and shoulder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
162
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(179 citation statements)
references
References 34 publications
8
162
2
7
Order By: Relevance
“…A study on patients with low back pain has also found prognostic factors to differ when varying outcome measures or different durations of followup were used (30). We found similar results in patients with hip and upper extremity complaints (31)(32)(33). This may be caused by different mechanisms that may underlie the recovery of pain and disability in patients with musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 68%
“…A study on patients with low back pain has also found prognostic factors to differ when varying outcome measures or different durations of followup were used (30). We found similar results in patients with hip and upper extremity complaints (31)(32)(33). This may be caused by different mechanisms that may underlie the recovery of pain and disability in patients with musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, the "initial pain intensity" factor was treated as a continuous variable in the regression analysis, and the findings revealed that the higher the initial pain intensity, the higher the risk of developing chronic nonspecific neck pain. The 37,38) . Bot et al (2005) reported that more intense pain at baseline significantly reduced the probability of recovery at 3 months in patients with neck and shoulder pain 37) .…”
Section: Discussionmentioning
confidence: 99%
“…The 37,38) . Bot et al (2005) reported that more intense pain at baseline significantly reduced the probability of recovery at 3 months in patients with neck and shoulder pain 37) . Campbell et al (2013) found that pain intensity experienced during a period of primary care consultation, and patients' perceptions about whether their back pain would persist, were significant predictors of poor outcome at 6 months and at 5 years in patients with low back pain 39) .…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58][59][60] It is possible that the patient may have improved because of the natural course of the disorder or other factors that were not measured or that we are unaware of. Because this was a single case report, it is not appropriate to generalize the effects from this patient to other patients with BJHS and spinal pain.…”
Section: Limitationsmentioning
confidence: 99%